CARBON DIOXIDE ABSORPTION FROM NATURAL GAS USING POTASSIUM CARBONATE PROMOTED WITH GLYCINE INCONTINUOUS PACKED COLUMN - MUSTAFA , NUR FARHANA AJUA (2020)
The data of continuous packed absorption system is important in order to understand on-site absorption process behavior. It is vital to ensure the process parameter specifically liquid flow rate, gas flow rate, operational pressure, CO2inlet concentration and liquid inlet temperature are operated at the most desirable condition for the maximum absorption performance. Besides, the fundamental properties such as liquid-film mass transfer coefficient,